Genetic evaluation of birth and weaning weight of Gudali and two-breed synthetic Wakwa beef cattle populations under selection in Cameroon: Genetic and phenotypic trends - Tawah, C.L.; Rege, J.E.O.; Mbah, D.A.; Oumate, H. (Cambridge University Press, 1994)
Breeding programmes for Wakwa and Ngaundere Gudali cattle breeds were initiated in Wakwa (Cameroon) in 1952 and 1965, respectively, to improve growth performance of the indigenous breedsAnimals were selected on 240-day weaning weight (WWT). Data analysed covered the period 1971 through 1985 and consisted of 2211 calf birth weight (BWT) and 1409 WWT records on Gudali and 1196 BWT and 763 WWT records on Wakwa. Selection responses in BWT and WWT were estimated as regressions of average sire estimated transmitting abilities (ETAs) and average dam estimated breeding values (EBVs) on year of calving. ETAs and EBVs were predicted using best linear unbiased prediction procedures. Estimated annual changes in sire ETAs for WWT were 0.67 and 1.69 kg/year for Gudali and Wakwa, respectively. Corresponding trends in dam EBVs were - 0.03 and - 0.24 kg/year. Estimated correlated trends in BWT among Gudali and Wakwa sire were 0.09 and -0.14 kg/year, respectively, corresponding correlated trends in BWT associated with dam selection were esentially zero, being -0.001 and 0.01 kg/year. Environmental trends were negative for all traits except Gudali WWT. Phenotypic trends were all positive, except that of Wakwa BWT. Overall, selection on WWT yielded moderate selection response despite substantial infrastructural constraints in the breeding programme. Trends in sire ETAs and dam EBVs for WWT jointly accounted for estiamted genetic gains of 8.60 kg in Gudali and 20.4 kg in Wakwa over the study period. Overall correlated response in BWT during the study period was significant and negative for Wakwa. It was positive but not significant for Gudali.